A rare presentation of perioperative myocardial infarction as a consequence of stent thrombosis in non-cardiac surgery - Kadakia, Aditi P.; Koli, Deepak C.; Mehta, Hemant H. (International Journal of Research in Medical Sciences, 2021)
Perioperative myocardial infarction (PMI) is a major cause of long term morbidity and mortality associated with non-cardiac surgery. In patients with recent coronary artery stent placement undergoing non-cardiac surgery perioperative management is always challenging. We reported an interesting case of a 67 year old man posted for head neck surgery with recent history of angioplasty with drug eluting stent developing perioperative MI and the challenges faced by an anaesthesiologist.